Assessment of management efficiency of city managers (based on focused interviews with entrepreneurs) - Alexander Borisovich Ponamarev (Вестник Майкопского государственного технологического университета)
The topic of the research is relevant to modern sociological science and social practice. The research problem lies, on the one hand, in the importance of the development of the municipality through contracts for municipal-private cooperation, and on the other hand, in the absence of a comprehensive scientific understanding of the barriers to the implementation of this process. The aim of the research is to assess the effectiveness of the management practices of city managers, in particular, their potential to attract private capital to the municipality. The methodological basis of the research in general theoretical terms is based on the new theory of institutions, in particular, on the concept of institutional evolution by D. North, and in the specific applied - focused interviews conducted with representatives of the business community and local administration in the Southern Federal District. As a result of the research, the following obstacles to the effective work of city managers have been identified: imitation practices, low qualifications of municipal employees, reduced trust of entrepreneurs, high economic risks and institutional instability. To overcome the above problems, the following recommendations have been made: to solve the problems of joining the law on PPP and MPP with anti-corruption legislation, to create a body to support MPP projects and increase business confidence in the municipality by setting clear «rules of the game» in the economic space.